Do patients value nutritional therapy? A quantitative study in type- 2 diabetes patients - Pinto, Ezequiel (2017)
Type 2 diabetes patients’ adherence to pharmacotherapy is higher than adherence to nutritional therapy or lifestyle change behaviours, and patients do not value nutritional therapy in the same level as they value other types of interventions. This study aimed to analyse the value that T2DM patients place on nutritional therapy and to identify perceived barriers to nutritional therapy adherence. Methods: A non-random sample of 62 patients receiving health care in a Diabetes Clinic in the municipality of Faro, in the Portuguese region of the Algarve, was interviewed with a semi-structured protocol regarding sociodemographic characteristics, lifestyle, physical activity, and dietary habits. Additional data were collected from the patient’s clinical files and by conducting anthropometric assessment using standard methods.